A high-quality genome assembly of Morinda officinalis, a famous native southern herb in the Lingnan region of southern China. (1st June 2021) - Wang, Jihua; Xu, Shiqiang; Mei, Yu; Cai, Shike; Gu, Yan; Sun, Minyang; Liang, Zhan; Xiao, Yong; Zhang, Muqing; Yang, Shaohai
Abstract: Morinda officinalis is a well-known medicinal and edible plant that is widely cultivated in the Lingnan region of southern China. Its dried roots (called bajitian in traditional Chinese medicine) are broadly used to treat various diseases, such as impotence and rheumatism. Here, we report a high-quality chromosome-scale genome assembly of M. officinalis using Nanopore single-molecule sequencing and Hi-C technology. The assembled genome size was 484.85 Mb with a scaffold N50 of 40.97 Mb, and 90.77% of the assembled sequences were anchored on eleven pseudochromosomes. The genome includes 27, 698 protein-coding genes, and most of the assemblies are repetitive sequences. Genome evolution analysis revealed that M. officinalis underwent core eudicot γ genome triplication events but no recent whole-genome duplication (WGD). Likewise, comparative genomic analysis showed no large-scale structural variation after species divergence between M. officinalis and Coffea canephora . Moreover, gene family analysis indicated that gene families associated with plant–pathogen interactions and sugar metabolism were significantly expanded in M. officinalis . Furthermore, we identified many candidate genes involved in the biosynthesis of major active components such as anthraquinones, iridoids and polysaccharides. In addition, we also found that the DHQS, GGPPS, TPS-Clin, TPS04, sacA, and UGDH gene families—which include the critical genes for active component biosynthesis—were expanded in M. officinalis . This study provides a valuable resource for understanding M. officinalis genome evolution and active component biosynthesis. This work will facilitate genetic improvement and molecular breeding of this commercially important plant.